Pengaruh Academic Burnout terhadap Prokrastinasi Akademik dalam Menyusun Skripsi pada Mahasiswa - Sabrina Babul Farkhah; Muhimmatul Hasanah; Prianggi Amelasasih (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Writing a thesis is not an easy thing, there are many obstacles that accompany it. Students who have difficulty controlling negative emotions due to writing a thesis will experience academic burnout, causing students to do academic procrastination in writing a thesis. This study aims to empirically examine the effect of academic burnout on academic procrastination in writing thesis for students at the University of Muhammadiyah Gresik. This study analyzed the data obtained from a sample of 46 people. The measuring instrument used is the Academic Burnout Scale and the Academic Procrastination Scale. The statistical analysis method used is simple linear regression analysis. The results of the partial test resulted in tcount = 12,902 more than t table = 2,015 with a significance (p) = 0.000 less than 0.05, which means that there is a significant effect of academic burnout on academic procrastination in writing thesis at Muhammadiyah University Gresik students with the effect of academic burnout on academic procrastination of 79.1%. The results of this research categorization indicate that the subject has a moderate category on academic procrastination and a moderate category on academic burnout.